2011
DOI: 10.1007/s12011-011-8990-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Developmental Exposure to TiO2 Nanoparticles on Synaptic Plasticity in Hippocampal Dentate Gyrus Area: an In Vivo Study in Anesthetized Rats

Abstract: With the increasing applications of titanium dioxide nanoparticles (TiO(2) NPs) in industry and daily life, an increasing number of studies showed that TiO(2) NPs may have negative effects on the respiratory or metabolic circle systems of organisms, while very few studies focused on the brain central nervous system (CNS). Synaptic plasticity in hippocampus is believed to be associated with certain high functions of CNS, such as learning and memory. Thus, in this study, we investigated the effects of developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…These findings indicate that the developmental brain is vulnerable to TiO 2 NP exposure, especially during the lactation period. 46 In addition, Mohammadipour et al 47 observed reduced hippocampal cell proliferation and decreased spatial memory, inhibitory memory, and learning ability in rat offspring after the maternal administration of TiO 2 NPs during pregnancy. In that study, rats were exposed to 100 mg/kg body weight of TiO 2 NPs every day, which is equivalent to ~6,000 mg/60 kg of body weight for humans, far lower than the LD 50 (dose required to kill 50% of a population of test animals) of TiO 2 for rats (12,000 mg/kg body weight) per the 1969 guidelines of the World Health Organization (WHO).…”
mentioning
confidence: 99%
“…These findings indicate that the developmental brain is vulnerable to TiO 2 NP exposure, especially during the lactation period. 46 In addition, Mohammadipour et al 47 observed reduced hippocampal cell proliferation and decreased spatial memory, inhibitory memory, and learning ability in rat offspring after the maternal administration of TiO 2 NPs during pregnancy. In that study, rats were exposed to 100 mg/kg body weight of TiO 2 NPs every day, which is equivalent to ~6,000 mg/60 kg of body weight for humans, far lower than the LD 50 (dose required to kill 50% of a population of test animals) of TiO 2 for rats (12,000 mg/kg body weight) per the 1969 guidelines of the World Health Organization (WHO).…”
mentioning
confidence: 99%
“…After an oral dose (100 mg/kg BW per day) administered to rats during gestation (GD 2-21) or lactation (PND 2-21), titanium was increased in the hippocampus. Lactational exposure attenuated synaptic plasticity in the hippocampus (associated with learning and memory), while a lesser effect was observed in the prenatally exposed offspring (Gao et al, 2011). We have reported previously that female offspring prenatally exposed to diesel exhaust particles (dams inhaled 19 mg DEP/m 3 1 h/day on GD 8-18) exhibited increased activity in the Open field (Hougaard et al, 2009).…”
Section: Developmental Neurotoxicitymentioning
confidence: 95%
“…As described in this chapter, changes in the brain and neurofunction are reported from animal studies of prenatal exposure to diesel exhaust and titanium dioxide particles. On the one hand, the developing brain may not be exposed to high doses of nanoparticles directly, due to restricted transport through several membrane barriers, even if nanoparticles have been observed in the brain of offspring weeks after prenatal exposure (Gao et al, 2011;Takeda et al, 2009). On the other hand, the developing brain may be especially vulnerable to nanoparticle induced oxidative stress, because of reduced anti-oxidant capacity in immature cerebral white matter, as suggested in .…”
Section: Developmental Neurotoxicitymentioning
confidence: 99%
“…34,35) Indeed, in mice, intravenously administered titanium dioxide nanoparticles with diameter of 8 nm and fullerenes have been shown to be transferred from dams to pups via breastfeeding. [36][37][38] Therefore, it is essential to examine infant exposure to nanoparticles via breastfeeding and breast milk. Studies are also needed to examine the potential for exposure of infants to nanoparticles at concentrations that are insufficient to cause biological effects in the mother, such as damage to the mammary gland.…”
Section: Distribution Of Nanoparticles In Breast Milk and The Effectsmentioning
confidence: 99%